anonymous
  • anonymous
Solve 3n-40=1/2n+35
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
n=30
abb0t
  • abb0t
\(\frac{a}{b} = \frac{e}{f} \Rightarrow af = eb\)
anonymous
  • anonymous
can u explain how you worked that out please?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Solve for n: 3 n-40 = n/2+35 Put the fractions in n/2+35 over a common denominator.
anonymous
  • anonymous
Solve for n: 3 n-40 = n/2+35 Put the fractions in n/2+35 over a common denominator. Put each term in n/2+35 over the common denominator 2: n/2+35 = n/2+70/2: 3 n-40 = n/2+70/2 Combine n/2+70/2 into a single fraction. n/2+70/2 = (n+70)/2: 3 n-40 = (n+70)/2 Move everything to the left hand side. Subtract (n+70)/2 from both sides of 3 n-40 = (n+70)/2: -40+3 n-(n+70)/2 = (n+70)/2-(n+70)/2 Look for two terms that sum to zero. (n+70)/2-(n+70)/2 = 0: -40+3 n-(n+70)/2 = 0 Put the fractions in -40+3 n-(n+70)/2 over a common denominator. Put each term in -40+3 n-(n+70)/2 over the common denominator 2: -40+3 n-(n+70)/2 = (-80)/2+(6 n)/2+(-70-n)/2: (-80)/2+(6 n)/2+(-70-n)/2 = 0 Combine (-80)/2+(6 n)/2+(-70-n)/2 into a single fraction. (-80)/2+(6 n)/2+(-70-n)/2 = (6 n+(-70-n)-80)/2: (6 n-n-80-70)/2 = 0 Group like terms in 6 n-n-80-70. Grouping like terms, 6 n-n-80-70 = (6 n-n)+(-80-70): ((6 n-n)+(-80-70))/2 = 0 Combine like terms in 6 n-n. 6 n-n = 5 n: (5 n+(-80-70))/2 = 0 Evaluate -80-70. -80-70 = -150: (5 n+-150)/2 = 0 Factor the polynomial, 5 n-150. Factor 5 from the polynomial 5 n-150: 5 (n-30)/2 = 0 Multiply both sides by a constant to simplify the equation. Multiply both sides of (5 (n-30))/2 = 0 by 2/5: ((2×5 (n-30))/(5))/(2) = 2/5×0 Express 2/5×0 as a single fraction. 2/5×0 = (2×0)/5: (2×5 (n-30))/(5×2) = (2×0)/5 Cancel common terms in the numerator and denominator of (2×5 (n-30))/(5×2). (2×5 (n-30))/(5×2) = (5×2)/(5×2)×(n-30) = n-30: n-30 = (2×0)/5 In (2×0)/5, divide 0 in the numerator by 5 in the denominator. 0/5 = (5×0)/5 = 0: n-30 = 2×0 Any number times zero is zero. 0×2 = 0: n-30 = 0 Isolate terms with n to the left hand side. Add 30 to both sides: n+(30-30) = 30 Look for two terms that sum to zero. 30-30 = 0:
anonymous
  • anonymous
thank you

Looking for something else?

Not the answer you are looking for? Search for more explanations.